Maternal adipokines and insulin as biomarkers of pregnancies complicated by overweight and obesity - Vernini, Joice Monaliza [UNESP]; Moreli, Jusciéle Brogin [UNESP]; Costa, Roberto Antônio Araújo [UNESP]; Negrato, Carlos Antonio [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema Mattos Paranhos [UNESP] (Springer Nature, 2016)
Background: Maternal obesity is associated with several adverse pregnancy outcomes. This study was conducted aiming to evaluate maternal levels of adipokines and insulin in pregnancies complicated by overweight and obesity and its correlations with maternal and fetal outcomes. Methods: This cross-sectional study included 72 mother-newborn pairs. Mothers were classified as having normal weight (n = 23), overweight (n = 18), and obesity (n = 31). Maternal adiponectin, leptin, resistin and insulin levels at the end of pregnancy were compared among groups and correlated with maternal and perinatal outcomes. Data were analyzed by ANOVA and correlation tests, with a p value <0.05 being considered as significant. Results: Obese pregnant women showed higher leptin levels (p = 0.0021). Leptin levels were positively correlated with prepregnancy body mass index - BMI (r = 0.57), gestational (37 or 38 weeks of gestation) BMI (r = 0.39), hypertension (r = 0.27), and hyperglycemia (r = 0.30), and negatively associated with newborns' abdominal circumference (r = -0.25). Adiponectin concentrations were negatively correlated with gestational BMI (r = -0.29) and newborns' cephalic circumference (r = -0.27) and positively correlated with birth weight (r = 0.23). Insulin concentrations correlated positively with prepregnancy BMI (r = 0.38), gestational BMI (r = 0.24) and maternal hyperglycemia (r = 0.26). Conclusions: Our findings support the relationship between markers of obesity and maternal-fetal outcomes. Maternal insulin and adipokines levels showed an independent relationship with mother and newborns outcomes, respectively. In this studied population, the results indirectly reinforce the importance of maternal weight control before and during pregnancy to avoid adverse outcomes to mother and their newborns.
Keywords: Adipokines; Hyperglycemia; Insulin resistance; Obesity; Pregnancy